Human paleopathology during the stone age - Katerina THEODORAKOPOULOU; Marianna KARAMANOU (Archives of the Balkan Medical Union, 2020)
Palaeopathology is a scientific tool which provides an integrated vision of diseases and lifestyle habits of ancient populations. This review paper aims to present an overview of the most common diseases of the Stone Age, their correlation with human habits and lifestyle, as well as their impact to health status of the prehistoric populations. Although the paleopathology of the Stone Age period is not well studied, we provide some indicative results of research works from Greek Neolithic archaeological sites. More paleopathological investigations are needed to have a satisfactory approach of the health status of prehistoric populations.